Fundamental Arbitrage under the Microscope: Evidence from Detailed Hedge Fund Transaction Data. (8th May 2021) - von Beschwitz, Bastian; Lunghi, Sandro; Schmidt, Daniel
Abstract: We exploit detailed transaction and position data for a sample of long-short equity hedge funds to study the trading activity of fundamental investors. We find that hedge funds exhibit skill in opening positions, but that they close their positions too early, thereby forgoing about one-third of the trades' potential profitability. We explain this behavior with the limits of arbitrage: hedge funds close positions early in order to reallocate their capital to more profitable investments and/or to accommodate tightened financial constraints. Consistent with this view, we document that hedge funds leave more money on the table after opening new positions, negative returns, or increases in funding constraints and volatility. ( JEL G11, G12, G14, G15)